IMPACT OF EATING PATTERNS ON URIC ACID LEVELS IN THE ELDERLY - Ningsih, Arum Dwi (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
The elderly as a population are at risk of having problems with decreasing body physiology, one of which is uric acid metabolism. One of the factors that influence an increase in uric acid levels is poor diet, namely foods with excessive purine content. The aim of this research is to determine the relationship between diet and uric acid levels in the elderly. The research design used is descriptive analytical research using a cross-sectional research approach. The population in this study were elderly posyandu participants in the working area of ​​the Kedundung Community Health Center, Mojokerto City. Sampling used the